Pengembangan Media Animasi Berbasis Microsoft PowerPoint Mata Pelajaran Bahasa Indonesia kelas III Sekolah Dasar - friendha yuanta (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2023)
This study focuses on developing animation media using Microsoft PowerPoint for Indonesian language lessons, specifically for third-grade students at SDN Putat Jaya 1 Surabaya. This study aims to develop a suitable and effective product for teaching fairy tales. The development method used is the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. Data was collected through the use of a questionnaire instrument. Data analysis included validity tests conducted by media experts, subject matter experts, the audience, and pretest and posttest assessments of students. The findings of this research on development show that animation media is considered appropriate, as indicated by the validity test conducted by media experts, which resulted in a result of 91.25%. Additionally, the media experts provided a result of 97.5%, while audience testing resulted in a score of 90%. Further, the pretest and posttest results showed an 8% improvement, confirming the efficacy of animation as a learning medium for third-grade elementary school students.